[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]=?

来源:学生作业帮助网 编辑:六六作业网 时间:2024/10/01 09:25:46
[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]=?[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]=?[(1-2i)^2/(3-4i)]-[(2+i)^2/(

[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]=?
[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]=?

[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]=?
[(1-2i)^2/(3-4i)]-[(2+i)^2/(4-3i)]
=[1-4-4i)/(3-4i)]-[(4-1+4i)/(4-3i)]
=-(3+4i)/(3-4i)-(3+4i)/(4-3i)
=-(3+4i)^2/[(3-4i)(3+4i)]-(3+4i)(4+3i)/[(4-3i)(4+3i)]
=-(9-16+24i)/(9+16)-(12+9i+16i-12)/(16+9)
=(7-24i)/25-(25i)/25
=7/25-24/25i-i
=7/25-49/25i